O ponto preto da serrapilheira: novas espécies, descrições suplementares e registros de distribuição de Corythalia C. L. Koch, 1850 (Araneae: Salticidae: Euophryini) - Alexandre Stamato Michelotto (2024)
Spiders are a megadiverse group of animals, which occur in all continents (except Antarctica), and which has originated million years ago. One of the lineages with the greatest adaptative success today is Salticidae Blackwall, 1841, the jumping spiders, with more than 6,600 species widespread across the globe. Among them, Euophryini Simon, 1901 stands out as the most diversified tribe and its genus Corythalia C. L. Koch, 1850 shows the greatest Neotropical diversity within the group. Corythalia are represented for small to medium-sized, black and white-striped spiders that forage mainly on soil and leaf litter in almost all of South and Central Americas. Recently, the South American species of the genus were revised, including the description of 20 new species. However, its wide diversity has not been fully revealed yet. In this study, six new species of Corythalia are described from Brazil, males and females of C. pequetita sp. nov., C. protoparva sp. nov. and males of C. delicata sp. nov., C. depressa sp. nov., C. cardoso sp. nov. and C. galeanoi sp. nov. We also describe for the first time the females of C. grata (Peckham & Peckham, 1901) and C. vervloeti Soares & Camargo, 1948 and the male of C. verhaaghi Bayer Höfer & Metzner, 2020. Eustiromastix efferatus Bauab-Vianna & Soares, 1978 is considered a junior synonym of Corythalia vervloeti Soares & Camargo, 1948 syn. nov., new distribution records of C. parva (Peckham & Peckham, 1901) are presented and charted.